2006
DOI: 10.2223/jped.1519
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of extended-spectrum beta-lactamase-producing <i>Klebsiella pneumoniae</i> in an intermediate-risk neonatal unit linked to onychomycosis in a healthcare worker

Abstract: Objective: To describe an outbreak of extended-spectrum betalactamase-producing Klebsiella pneumoniae in an intermediate-risk neonatal unit. Methods:After the identification of the first cases, the situation was regarded as an outbreak, and basic preventive measures against nosocomial infections were strictly enforced, and possible sources of dissemination were investigated. Results:The outbreak lasted for 6 months and affected 36 newborn infants, causing seven infections and 29 colonizations. In the first sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 9 publications
0
6
0
5
Order By: Relevance
“…There is a paucity of information about outbreaks in intermediate risk neonatal units 5 . Here we describe the clinical features and drug sensitivity pattern of Klebsiella pneumoniae infection in an intermediate risk, level 2 neonatal care unit (Sick Newborn Care Unit) 6 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of information about outbreaks in intermediate risk neonatal units 5 . Here we describe the clinical features and drug sensitivity pattern of Klebsiella pneumoniae infection in an intermediate risk, level 2 neonatal care unit (Sick Newborn Care Unit) 6 .…”
Section: Discussionmentioning
confidence: 99%
“…A intervenção no surto de K. pneumoniae ESBL foi fundamental: a limitação de sua disseminação auxiliou na redução dos índices de morbidade e mortalidade por esse agente patológico. [10][11][12][13][14]20,21 As notificações dos casos de K. pneumoniae ESBL diminuíram sensivelmente após a implantação da intervenção e manutenção das ações de prevenção de IRAS na UTI neonatal da maternidade estudada. A intervenção baseou-se na terapia medicamentosa para a onicomicose com o medicamento ciclopirox 8% (esmalte), aplicado três vezes por semana, durante seis semanas, e no lixamento da unha afetada antes da aplicação do fármaco pela primeira vez e uma vez por semana, para facilitar a atuação do medicamento nas mãos dos funcionários da UTIN.…”
Section: Discussionunclassified
“…Trata-se de um microrganismo residente que se aloja na flora do trato gastrointestinal dos recém-nascidos e que, nos últimos anos, responde cada vez menos ao tratamento com antibióticos devido à existência de cepas produtoras da enzima betalactamase de espectro expandido (ESBL), a qual destrói um grande número de antibióticos. [10][11][12][13][14] Considerando-se a importância das infecções por bactérias do gênero Klebsiella, a ocorrência de surto de infecção relacionada à assistência à saúde (IRAS) por esse agente e a experiência divulgada na literatura, 14 que associa a persistência da colonização por esse microrganismo à onicomicose na mão de trabalhadores de saúde responsáveis pelo cuidado direto dos recém-natos, este artigo teve como objetivo descrever os procedimentos adotados na intervenção de um surto de K. pneumoniae ESBL relacionado aos trabalhadores de UTI neonatal na cidade de Teresina, estado do Piauí, Brasil, no período de 2010 a 2011.…”
Section: Introductionunclassified
“…7 Wearing artificial acrylic fingernails and inadequate hand hygiene can also result in hands remaining contaminated with pathogens after use of either soap or alcohol-based hand gel 8 and has been associated with outbreaks of infection. 9 Correlation between hand hygiene and health care associated infections Designing randomized controlled trials of hand hygiene as an independent factor in reducing HCAIs are difficult and not practical. However, studies have reported that following the implementation of hand hygiene multimodal strategies, a significant decrease of overall HCAI rates in neonatal ICUs 10,11 and positive outcomes are reported among very low-birthweight neonates 12 and also on specific types of HCAI such as rotavirus.…”
Section: Cross-transmission Of Organisms By Contaminated or Incompletmentioning
confidence: 99%